Preliminary Results of the 2013 Republic of Srpska Population Census and the Comparison with the Previous 1991 Census - Draško Marinković; Rajko Vranješ (Демографија, 2013)
The population, households, and dwellings census is the crucial statistical source of specific data on a country's population. There has been an official census in Bosnia and Herzegovina, and its Republic of Srpska entity, after 22 years. The period between the two censuses has seen many administrative-territorial, social-economic, and demographic changes. There is a matter of methodological comparison between the 1991 and 2013 censuses due to huge administrative-territorial alterations with reference to municipalities and settlements. The preliminary 2013 census results indicate a vast decrease in population within the area of the Republic of Srpska.